2001
DOI: 10.1074/jbc.m010930200
|View full text |Cite
|
Sign up to set email alerts
|

The Epithelium-specific ETS Protein EHF/ESE-3 Is a Context-dependent Transcriptional Repressor Downstream of MAPK Signaling Cascades

Abstract: Exon trapping and cDNA selection procedures were used to search for novel genes at human chromosome 11p13, a region previously associated with loss of heterozygosity in epithelial carcinomas. Using these approaches, we found the ESE-2 and ESE-3 genes, coding for ETS domain-containing transcription factors. These genes lie in close proximity to the catalase gene within a ϳ200-kilobase genomic interval. ESE-3 mRNA is widely expressed in human tissues with high epithelial content, and immunohistochemical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 61 publications
6
88
1
Order By: Relevance
“…32 Functionally, this protein has been shown to be a transcriptional repressor of several genes positively regulated by MAP kinase signaling. 33 As ascertained by western blotting, ESE-3 protein was completely eliminated in nuclear extracts obtained from APCs stimulated with various TLR ligands and incubated with IL-10 ( Figure 4).…”
Section: Il-10 Inhibits Tlr-mediated Activation Of Apcsmentioning
confidence: 86%
“…32 Functionally, this protein has been shown to be a transcriptional repressor of several genes positively regulated by MAP kinase signaling. 33 As ascertained by western blotting, ESE-3 protein was completely eliminated in nuclear extracts obtained from APCs stimulated with various TLR ligands and incubated with IL-10 ( Figure 4).…”
Section: Il-10 Inhibits Tlr-mediated Activation Of Apcsmentioning
confidence: 86%
“…Together with our finding that ESE-3 is upregulated by cytokines in bronchial epithelial cells, this supports the idea that ESE-3 may play a role in the pathogenesis of asthma. It has been shown that ESE-3 represses expression of the matrix metalloproteinase MMP-1 [18,26]. MMPs mediate extracellular matrix remodeling during processes such as wound repair [40,41].…”
Section: Ese-3mentioning
confidence: 99%
“…Many Ets family members are expressed in hematopoietic cells [13]. However, the three ESE transcription factors are expressed only in organs that have specialized epithelial cells, such as intestine, kidney, prostate, pancreas and lung [8,9,[14][15][16][17][18][19][20]. ESE-1 is expressed in many different organs, whereas ESE-2 and ESE-3 expression is more restricted to the glandular organs, such as the salivary gland, mammary gland and prostate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, more than 30 Ets family members have been identified [2,3]. These proteins are expressed mainly in hematopoietic cells [4,5], however some are also expressed in epithelial cells [6][7][8][9][10][11]. Ets factors are known to play roles in skeletal development, haematopoiesis, neural synapse formation, immunomodulation, metastasis, cellular proliferation and differentiation, and apoptosis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%